2018
DOI: 10.1590/s0004-2803.201800000-46
|View full text |Cite
|
Sign up to set email alerts
|

Functional Constipation and Overactive Bladder in Women: A Population-Based Study

Abstract: Functional constipation is associated with overactive bladder and its dry subtype, particularly in the younger population. In addition, this association is responsible for lower quality of life scores, especially when urinary incontinence is present. The presence of manual maneuvers and less than three defecations per week should direct us to look for overactive bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Some published data suggest that Hispanic people have a higher risk of moderate or severe LUTS compared with Caucasians 8 . The few published studies of Latin American populations have provided epidemiological data, while overlooking the impact of OAB on work, QoL, and treatment-seeking behavior [9][10][11][12][13][14] . The Colombian Overactive Bladder and Lower urinary Tract symptoms (COBaLT) study of 1060 individuals aged 18-89 years found that OAB was reported by 31.8% of participants and had a severe effect on their QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Some published data suggest that Hispanic people have a higher risk of moderate or severe LUTS compared with Caucasians 8 . The few published studies of Latin American populations have provided epidemiological data, while overlooking the impact of OAB on work, QoL, and treatment-seeking behavior [9][10][11][12][13][14] . The Colombian Overactive Bladder and Lower urinary Tract symptoms (COBaLT) study of 1060 individuals aged 18-89 years found that OAB was reported by 31.8% of participants and had a severe effect on their QoL.…”
Section: Introductionmentioning
confidence: 99%
“…O aumento do peso corporal e abortos anteriores acabam se tornando fatores contribuintes para o aparecimento da IUE durante este período (18,22) . Estudos encontraram resultados semelhantes sobre o nível socioeducacional, apontando uma baixa instrução (23)(24) . O percentual elevado para mulheres do lar neste estudo, 138 (60,8%), também foi observado em outras pesquisas (3,21) .…”
Section: Discussionunclassified
“…Accordingly, lifestyle modifications aimed at reducing smoking and dietary triggers can result in an improvement of OAB [28]. Finally, an association between functional constipation and OAB has been shown [29][30][31], but these studies do not specifically report on the effect of treating constipation and relief of OAB.…”
Section: First-line Therapymentioning
confidence: 99%